Implementation of the Youth Preference and Reservations Policy in Public Procurement: The Case of State Owned Enterprises in Nairobi - Thairu, Julius; Chirchir, Dr. Michael (International Journal of Supply Chain Management, 2016)
Purpose: The purpose of this study was to determine the implementation of the youth preference and reservations policy in public procurement. The research questions therefore were; to establish the extent to which the youth preference and reservations policy has been implemented and to establish the extent to which institutional challenges and legislation respectively affect implementation of the policy. Methodology: The study employed descriptive survey design and a census of all the 70 state owned enterprises headquartered in Nairobi was conducted in the study out of which 55 enterprises responded. The study used primary data which was collected through use of a five point likert scale questionnaire. The researcher used Statistical Package for Social Sciences (SPSS) to generate the descriptive statistics and also to generate inferential results. The descriptive statistics used included frequencies, averages and percentages while inferential statistics such as correlation analysis was used to demonstrate the extent to which legislation affects implementation of the youth preference and reservations policy in public procurement. Results: According to the research findings, the youth preference and reservations policy in public procurement had not been fully implemented. Effects of institutional challenges on implementation were found to be statistically significant with a negative impact on the implementation of the youth preference and reservations policy in public procurement. Results also indicate that legislation had negative but significant effect on implementation of the youth preference and reservations policy in public procurement. Unique contribution to theory, practice and policy: The study recommends that the government intensifies the awareness campaign among the procurement practitioners and budget holders on the policy; institutionalize monitoring and training in all the enterprises and include the practitioners in review of the Public Procurement legislation.